School Counselling System In The Czech Republic - Ehlová, Marcela (My University, 2022)
The article deals with the issue of school counselling in the Czech Republic. It informs about the activities of the school counselling centre and characterizes the work of educational advisers, school prevention specialists, school psychologists and special school educators in contemporary schools. In conclusion, current trends are outlined that lead to the professionalization of school counselling and ensure better conditions for the education of pupils with special educational needs.
Školní poradenský systém v České republice
Keywords: school counselling; educational advisers; school prevention specialists; school psychologists; special school educators; students with special educational needs; školní poradenství; výchovný poradce; školní metodik prevence; školní psycholog; školní speciální pedagog; žáci se speciálními vzdělávacími potřebami